2016
DOI: 10.1088/1054-660x/26/3/035601
|View full text |Cite
|
Sign up to set email alerts
|

Low-level lasers affect uncoupling protein gene expression in skin and skeletal muscle tissues

Abstract: Wavelength, frequency, power, fluence, and emission mode determine the photophysical, photochemical, and photobiological responses of biological tissues to low-level lasers. Free radicals are involved in these responses acting as second messengers in intracellular signaling processes. Irradiated cells present defenses against these chemical species to avoid unwanted effects, such as uncoupling proteins (UCPs), which are part of protective mechanisms and minimize the effects of free radical generation in mitoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…UCP2 mRNA plays a key role as a sensor of mitochondrial oxidative stress [29], protecting cells against overproduction of mitochondrial reactive oxygen species [30]. In this aspect, our findings agree that reactive oxygen species are involved in laser-induced effects [31] and reinforce that low-level lasers increase the UCP2 mRNA levels to protect cells against oxidative damage [26].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…UCP2 mRNA plays a key role as a sensor of mitochondrial oxidative stress [29], protecting cells against overproduction of mitochondrial reactive oxygen species [30]. In this aspect, our findings agree that reactive oxygen species are involved in laser-induced effects [31] and reinforce that low-level lasers increase the UCP2 mRNA levels to protect cells against oxidative damage [26].…”
Section: Discussionsupporting
confidence: 78%
“…On the other hand, studies have demonstrated that increased mir-15a levels decrease UCP2 mRNA levels [20]. Previous results demonstrated that exposure to low-level lasers increases UCP2 mRNA levels in skin and skeletal muscle tissue from Wistar rats [26]. However, despite no alteration of mir-15a levels, our findings show that MDA-MB-231 cells exposed to a lowlevel red laser (figure 3) present increased UCP2 mRNA levels at the lower fluence (25 J cm −2 ) and low-level infrared laser exposure increases UCP2 mRNA levels in these cells at the higher fluence (50 J cm −2 ) (figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…Low-level red and infrared lasers, into the so-called therapeutic window (600 up to 1100 nm), are able to induce molecular effects, which are used in clinical protocols for the treatment of a number of diseases in phototherapy [25,26] and photodynamic therapy [27][28][29]. As these molecular effects are not yet understood, mainly gene expression, RT-qPCR has been used to evaluate laser-induced effects on mRNA levels [30,31]. However, an adequate reference gene is necessary when taking into account the biostimulation (or biomodulation) effect induced by exposure to low-level lasers [12].…”
Section: Discussionmentioning
confidence: 99%
“…tissues-UCP2 and UCP3 (uncoupling protein) mRNA gene relative expression in the skin and skeletal muscle tissues of Wistar rats exposed to low-level red and infrared lasers is evaluated [37]. • Biospeckle technique for the non-destructive differentiation of bruised and fresh regions of an Indian apple using intensity-based algorithms-in a rigorous comparison, a number of algorithms are applied to differentiate the bruised and fresh regions of an Indian apple through biospeckle technique during its 9 day shelf life [38].…”
Section: • Low-level Lasers Affect Uncoupling Protein Gene Expression...mentioning
confidence: 99%